Propensity score–weighted analysis of chemotherapy after PD-1 inhibitors versus chemotherapy alone in patients with non–small cell lung cancer (WJOG10217L) - Nobuyuki Yamamoto; Ryoji Kato; Hidetoshi Hayashi; Yasutaka Chiba; Eriko Miyawaki; Junichi Shimizu; Tomohiro Ozaki; Daichi Fujimoto; Ryo Toyozawa; Atsushi Nakamura; Toshiyuki Kozuki; Kentaro Tanaka; et al. (Journal for ImmunoTherapy of Cancer)
Background Studies have suggested that chemotherapy after immune checkpoint inhibitors may confer an improved response for non–small cell lung cancer (NSCLC). However, potential selection bias in such studies has not been addressed. We therefore applied propensity score analysis to investigate the efficacy of chemotherapy after PD-1 inhibitor treatment (CAP) compared with chemotherapy alone.Methods We conducted a retrospective observational cohort study for patients treated at 47 institutions across Japan between April 1, 2014 and July 31, 2017. Eligible patients had advanced or recurrent NSCLC who have undergone chemotherapy. Patients subsequently treated with chemotherapy (docetaxel with or without ramucirumab, S-1 or pemetrexed) either after PD-1 inhibitor therapy (CAP cohort) or alone (control cohort) were included. The primary end point was objective response rate (ORR). Inverse probability weighting (IPW) was applied to adjust for potential confounding factors.Results A total of 1439 patients (243 and 1196 in the CAP and control cohorts, respectively) was available for unadjusted analysis. Several baseline characteristics—including age, histology, EGFR or ALK genetic alterations, and brain metastasis—differed significantly between the two cohorts. After adjustment for patient characteristics with the IPW method, ORR was 18.9% for the CAP cohort and 11.0% for the control cohort (ORR ratio 1.71; 95% CI 1.19 to 2.46; p=0.004). IPW-adjusted Kaplan-Meier curves showed that median progression-free survival (PFS) for the CAP and control cohorts was 2.8 and 2.7 months (IPW-adjusted HR 0.95; 95% CI 0.80 to 1.12; p=0.55), and median overall survival (OS) was 9.2 and 10.4 months (IPW-adjusted HR 1.05; 95% CI 0.86 to 1.28; p=0.63), respectively.Conclusions After accounting for selection bias by propensity score analysis, CAP showed a significantly higher ORR compared with chemotherapy alone, with the primary end point of ORR being achieved. However, these results did not translate into a PFS or OS advantage, suggesting that prior administration of PD-1 inhibitors may result in a synergistic antitumor effect with subsequent chemotherapy, but that such an effect is transient. CAP therefore does not appear to achieve durable tumor control or confer a lasting survival benefit.